Forecasting Agricultural Engineering Manpower Requirement in India - Nanda, S. K.; Agrawal, Rashmi; Rao, D. Rama; Awasthi, I. C. (Journal of Agricultural Engineering, 2013)
The growth of agricultural engineering human capital in India is critical to growth and development in agriculture and its allied sectors. A comprehensive assessment of demand-supply scenario for agricultural engineering human capital in India was thus attempted. Mixed forecasting approaches were used to estimate current stock and future demand. The forecasts were made under various growth conditions. The annual demand was computed by integrating independent stock projections in different sub-sectors of employment. During 2001-2010, the annual supply of agricultural engineering graduates in India increased from about 630 to 1500 at an annual compound growth rate of 10 percent. The requirement would be for about 3500 graduates by 2020. The demand for PG/Ph.D is much higher than for UGs. In addition, there is growing need and demand for about 3,000 diploma holders against none at present. With growth in mechanisation and diversification in food processing sectors, there is a need for more agri-engineering professionals and para-professionals in the country. The forecast estimates required outturn growth of 5% in UG, 10% in PG and 20% in Ph.D level education.